Does â€œYâ€ Generation Managers Attributes is Associated with Technology Adoption Behavior? - Normala, Normala; ., Dileep Kumar M. (Information Management and Business Review, 2013)
It is a dilemma to professionals that whether they should adopt technology to improve their functional contributions and thereby enhance business performance. Changes in the generations have different approaches to adopt technology application in their work life. As we see the differences in Generation X and Generation Y, in their features and characteristics, it is hypothesized that such differences also expect in professional approach in the adoption of technology for effective functional dissemination. This particular study follows a qualitative research methodology that to explore the relationship between Generation Y professionals in their attitude towards adoption of technology in business operations.